Distortions to Agricultural Incentives : A Global Perspective, 1955-2007 - Anderson, Kym (Washington, DC: World Bank and Palgrave Macmillan, 2012)
This book provides an overview of the evolution of distortions to agricultural incentives caused by price, trade, and exchange rate policies in a large sample of countries spanning the world. This chapter begins with a brief summary of the long history of national distortions to agricultural markets. It then outlines the methodology used to generate annual indicators of the extent of government interventions in markets, details of which are provided in Anderson et al. (2008a, 2008b) and appendix A of this volume. A description of the economies being examined and their economic growth and structural changes over recent decades is then briefly presented as a preface to the main section of the chapter, in which the nominal rate of assistance (NRA) and consumer tax equivalent (CTE) estimates are summarized across regions and over the decades since the 1950s. These estimates are discussed in far more detail in the regional studies that follow, chapters two-ten. A summary of an additional set of indicators of agricultural price distortions, presented in chapter eleven, is based on the trade restrictiveness index first developed by Anderson and Neary (2005). In chapter twelve, the focus shifts from countries to commodities, and various distortion indicators are used to provide a sense of how distorted each of the key farm commodity markets is globally. Chapter thirteen uses the study's NRA and CTE estimates to provide a new set of results from a global economy-wide model. It quantifies the impacts of reforms undertaken since the early 1980s, and of the policies still in place as of 2004, on global markets, net farm incomes, and welfare. Finally, that chapter concludes by drawing on the lessons learned to speculate on the prospects for further reducing the disarray in world agricultural markets.